The proportion and clinical characteristics of patients with stroke who returned to work six months after discharge from a convalescent rehabilitation ward: a descriptive study - Yamamoto, Takashi; Wada, Yoshitaka; Maeda, Hirofumi; Matsuura, Daisuke; Hirano, Satoshi; Shibata, Seiko; Mukaino, Masahiko; Otaka, Yohei (Frontiers in Rehabilitation Sciences, 2025)
BackgroundThe economic burden on individuals with stroke is a major concern, and measures to mitigate the negative effects of stroke on labor productivity are imperative. However, few studies have explored the return to work (RTW) of individuals with stroke after their discharge from rehabilitation wards. We therefore aimed to explore the proportion of patients with stroke who returned to work after discharge from a convalescent rehabilitation ward and to explore the characteristics of patients with stroke who achieve RTW compared to those who do not.MethodsThis descriptive study was conducted in a convalescent rehabilitation ward at a university hospital in Japan. It included patients with stroke in the working-age population (15–64 years) who worked before the onset and were discharged from the rehabilitation ward to their homes between January 2018 and April 2022. The participants were required to respond to a questionnaire, which was sent by mail, and the RTW status at 6 months after discharge from the rehabilitation ward was investigated. They were classified into RTW and non-RTW groups, and their characteristics were compared between the groups.ResultsFifty-nine patients [mean (SD) age 53.0 (9.0) years; 42 men] among 125 who met the criteria returned the questionnaire, and their data were included in the analysis. Thirty-nine individuals [66.1%; mean (SD) age 53.0 (8.2) years; 31 men] achieved RTW. Compared to the non-RTW group, the RTW group had significantly higher total functional independence measure (FIM) scores at admission (p = 0.046) and discharge (p < 0.001), a significantly shorter duration of ward stay during hospitalization (p = 0.002), and a significantly smaller proportion of patients with aphasia (p = 0.019).ConclusionTwo-thirds of the patients in this study population had achieved RTW at 6 months after discharge from the convalescent rehabilitation ward. Patients who achieved RTW had better motor function and FIM scores at discharge than those who did not.